Measurement of the charge asymmetry in semileptonic B-s(0) decays - Abazov, V. M.; Abbott, B.; Abolins, M.; Acharya, B. S.; Adams, M.; Adams, T.; Aguilo, E.; Ahn, S. H.; Ahsan, M.; Alexeev, G. D.; Alkhazov, G.; Alton, A.; et al. (American Physical Soc, 2007)
We have performed the first direct measurement of the time-integrated flavor untagged charge asymmetry in semileptonic B-s(0) decays A(SL)(s,unt) by comparing the decay rate of B-s(0) -> mu(+) D-s(-) nu X, where D-s(-) -> phi pi(-) and phi -> K+K-, with the charge-conjugate (B) over bar (0)(s) decay rate. This sample was selected from 1: 3 fb(-1) of data collected by the D0 experiment in run II of the Fermilab Tevatron collider. We obtain A(SL)(s,unt) = [1.23 +/- 0.97(stat) +/- 0.17(syst)] x 10(-2). Assuming that Delta m(s)/(Gamma) over bar (s) >> 1, this result can be translated into a measurement of the CP-violating phase in B-s(0) mixing: Delta Gamma(s)/Delta m(s) tan phi(s) = [2.45 +/- 1.93(stat) +/- 0.35(syst)] x 10(-2).